Bank branching and corporate tax avoidance: Evidence from a quasi-natural experiment of banking deregulation in China - Xiaoxia Li; Tong Zhou (China Journal of Accounting Studies (CJAS), 2024)
Using the small and medium-sized commercial banks' market entry reform policy implemented in 2009 in China as a quasi-natural experiment of banking deregulation, we examine its effect on corporate tax avoidance. Our empirical results show that banking deregulation significantly reduces corporate tax avoidance. Banking deregulation not only promotes the expansion of joint-stock banks and city commercial banks, but also increases the credit supply and bank competition in the region. Further tests imply that banking deregulation restrains corporate tax avoidance through two channels: alleviating financial constraints and strengthening external monitoring. Our paper sheds new light on the spillover effects from regulations in the banking sector to tax management behaviours in the corporate sector.
Keywords: 650; Banking deregulation; corporate tax avoidance; external monitoring; financial constraints; financial supply side reform